Phosphate solubilizing and PGR activities of ericaceous shrubs microorganisms isolated from Mediterranean forest soil. (May 2019) - Hamim, Ahlam; Boukeskasse, Amal; Ouhdouch, Yedir; Farrouki, Abderhmane; Barrijal, Said; Miché, Lucie; Mrabet, Rachid; Duponnois, Robin; Hafidi, Mohamed
Abstract: Many soil microorganisms are able to transform insoluble forms of phosphorus into an accessible soluble form, thus contributing to plant nutrition through exhibiting other beneficial traits such as production of organic acids, siderophore indole acetic acid (IAA) and production of hydrogen cyanide (HCN). Achieving this purpose, ericoid fungi and actinobacteria were isolated from roots and rhizospheric soil of Calluna vulgaris L., belonging to the ericaceous family. All isolates were shown to be able to solubilize insoluble phosphate in liquid cultures and to produce transparent halos of solubilization on PVK solid medium. The actinobacteria isolate AH6 was the most efficient compared to others, producing 145.5 mg/L of phosphate and 141 μg/L of IAA. However, fungi isolate S2 and S3 had high solubilization capacity and produced a high concentration of IAA in comparison with S1, which was a good siderophore producer. We applied a sequencing approach by amplifying the ITS region for fungi and 16S for actinobacteria. Most of the actinobacteria isolates belong to the Streptomyces genus while fungi were identified as related to ericoid mycorrhizal fungi. To evaluate the effectiveness of selected rhizobacteria and symbiotic fungi isolates and to confirm their role as biofertilizers, inoculation experimentations on plants are required.